La pedagogía por proyectos, basada en el Informe de la Comisión de la Verdad, para el fortalecimiento de la escritura académica (Memorias Sifored - Encuentros Educación UAN, 2023)
This article reflects on mother tongue academic writing in different students ́educational levels. The study's main objective is to strengthen academic writing in students of 5th grade of elementary school, 11th grade of high school and higher education through the implementation of Pedagogy by Projects based on the Truth Commission Report. A qualitative, quasi-experimental study was conducted with a pre and post test, in order to identify strengths and weaknesses in the students ́writing process. The comparative analytical result evidences a significant improvement in the students' writing processes by understanding how the reelaboration of the text allows strengthening the communicative competence and especially the oral and written textual production. The study concludes that the Pedagogy by Projects  based on the Truth Commission Report constitutes not only a key pedagogical tool for strengthening writing in students of 5th grade of elementary school, 11th grade of high school and higher education, but also a space for dialogue and reflection in the classroom.
Keywords: Teacher training; Pedagogy by Projects; academic writing; pedagogical experience; soliloquy